The Impact caused by the natural disaster in Malaysia: Food and Landslide - Yong, Yoong Kee (2013)
Natural disaster is the consequence of the combination of the natural hazard and human activities, human vulnerability, caused by the lack of appropriate emergency management, leads to financial structural and human losses. In Malaysia, there are many kind of natural disaster attack to our country every year, but there are two major disaster that attacking our country, it is flood and landslide, especially flood event, every year we have encountered flood event, e.g. The flooding of the Kuala Lumpur in the 1970 caused serious damage to the lives and properties and called for flood mitigation schemes in Kuala Lampur. In construction industry, the landslide and flood event keep climbing up year by year. There is many sources give rise to the landslide and flood event, people should pay attention and put awareness on it, this is because some its cases can be avoid or reduce like inadequate drainage system, over development, design error and so on. If the flood and landslide event incessancy attack to ours country, for sure there will cause some issue like finance los, life been threated, image of the country also affected, people lose confidence toward the government, GDP of our country also fall down In this thesis also showing the comparison of the contract clause in PAM, PWD and others standard form. For sure, there is some of the method to reduce or avoid the natural event like the landslide and flood. this two natural disaster event has some similar way, they always have related with water, so to reduce this problem, and we constructed a proper damage system to fulfil the rain water and so on. Sometimes we may have constructed a proper drainage system, but after certain year, when people the population is increase, the over development will cause the system out of service, so we need to upgrade the system and do the maintenance frequently, nevertheless, government should recognize some talk to increase the awareness of the public and set more strict rules in apply to staert the project in site like revise the term and condition in PAM to make it more detail. In construction industry, the developer can transfer the risk to contractor and the contractor can transfer the risk to insurance company and sub-contractor. When the risk is prohibit to transfer, contractor can done some safety assessment before start the project to make sure the site is under control and safety. In conclusion, people should put awareness on the landslide and flood, there is the some mitigation method to reduce or avoid it like build smart tunnel or retaining wall, life is more important then everything. Some project spend less in quality improvement, it may bring a lot of problem in the future. Since the landslide and flood event is frequent attack to our country, we may contract the building that can reduce the natural disaster event like construct more bigger dam, high quality of retaining wall and so on.